Business Income, Operational Costs, and Production Costs on Net Profit After Tax at PT Unilever Indonesia Tbk Period 2016 - 2021 - Purnama, Intan; Diana; Yani, Fitri (First Ciera Publisher, 2023)
This study aims to determine the effect of operating income, operating costs, and production costs on net income. This research was conducted on the company PT. Unilever Indonesia Tbk which is listed on the Indonesia Stock Exchange (IDX) for the 2016-2021 period. The population in this study is the Financial Statements of PT. Unilever Indonesia Tbk which is published at https://www.unilever.co.id. The sample in this study is the Quarterly Financial Statements of PT. Unilever Indonesia Tbk from 2016-2021 where the sample in this study totaled 24 financial reports. Data analysis using multiple linear regression. The results of the study explain that operating income has a significant positive effect, operational costs have a significant negative effect, and production costs have a significant negative effect on net profit after tax, which means that if production costs decrease, there will be an increase in net profit of PT.Unilever Indonesia Tbk.